The Disintegration of Memphis-Shelby County, Tennessee: School District Secession and Local Control in the 21st Century. (August 2018) - Siegel-Hawley, Genevieve; Diem, Sarah; Frankenberg, Erica
In this qualitative case study, we explore the political impulses behind suburban secession from the 2013 Memphis-Shelby County merger, the largest school district consolidation in recent history. Decades removed from the Civil Rights Movement, during a period of stark inequality, colorblind law and policymaking, and a diminished understanding of education as a societal benefit, the central suburban rationale for secession, local control, carries new weight. It gives already privileged communities a race-neutral, legally sanctioned, and politically persuasive way to discuss resource accumulation that maps onto existing racial and economic segregation. Memphis-area lessons offer insight into an increasing number of secession struggles and enrich our understanding of how educational advantage is consolidated in the 21st-century metropolis.